PIRACY AROUND AFRICA’S WEST AND EAST COASTS: A COMPARATIVE POLITICAL PERSPECTIVE - Neethling, Theo (Scientia Militaria - South African Journal of Military Studies, 2011)
The study of politics, or political science, focuses on both the abstract theories and practical operation of government and politics. The phenomenon of piracy on the east and west coasts of Africa brings an important scholarly issue to the fore, namely the significant roles of non-state actors in national, regional and global issues and politics. The phenomenon of maritime piracy along Africa’s coastal areas is indeed of great strategic and political-economic interest ? specifically since globalisation and maritime trade show a close interface. This article examines the similarities and differences relating to the phenomenon of piracy on the east and west coasts of Africa from a Political Science perspective by assessing, interpreting and appraising the phenomenon, and ascribing meaning to recent events and developments. It also explains the current insecurity off the west and east African coasts and closes with a brief comparison between the two regions under review. It concludes with the point that most security challenges confronting Africa have their origin in the lack or failure of governance as states are the primary actors and agents of good order at sea. Thus the required good order at sea should be viewed as a function of how states, such as Somalia and Nigeria, exercise their jurisdiction at sea to secure busy sea lanes and also to protect the safe harvesting and extraction of resources.